Online or in‐class problem based learning: Which one is more effective in enhancing learning outcomes and critical thinking in higher education EFL classroom? - Orhan, Ali (Journal of Computer Assisted Learning, 2024)
Background: Although problem based learning has a great potential to promote learning outcomes as well as cognitive abilities, the number of previous studies investigating this potential on critical thinking, reading comprehension abilities and attitudes in English as a Foreign Language (EFL) context is scarce. Also, the number of studies comparing the effectiveness of online and face‐to‐face problem based learning on these variables is scarcer and this limited research has yielded contradictory results. Objectives: This study aimed to investigate and compare the effectiveness of online and face‐to‐face problem based learning on critical thinking skills, dispositions, reading comprehension abilities, and attitudes of EFL students. Method: Pretest‐posttest control group quasi‐experimental design was employed in this study that has two experimental groups and one control group. There were 23 (13 females and 10 males), 23 (14 females and 9 males), and 22 (12 females and 10 males) EFL students in online problem based learning group, face‐to‐face problem based learning group, and control group, respectively. In the first experimental group, problem based learning activities were conducted online while the same activities were conducted face‐to‐face in the classroom in the second experimental group. In the control group, no experimental procedures were followed and the students continued their regular instructor‐led reading activities. Watson‐Glaser Critical Thinking Test, Sosu Critical Thinking Dispositions Scale, Reading Comprehension Test, and Attitudes Towards English Scale were used to collect the data. The data were analysed using paired‐samples t‐test and ANCOVA with pretest scores as the covariate variable. Results and Conclusions: It was found that problem based learning, either online or face‐to‐face, significantly enhanced EFL learners' reading comprehension abilities and attitudes towards English as well as their critical thinking skills and dispositions. It was also concluded that online problem based learning is more effective to enhance reading comprehension abilities and attitudes than face‐to‐face problem based learning while they are equally effective in promoting critical thinking skills and dispositions in EFL classroom. Implications: This study has significant implications for educators and researchers. As this study showed that online problem based learning is a promising alternative to face‐to‐face problem based learning, universities, educators, administrators, and researchers can organize their problem based learning activities online to promote learning outcomes and cognitive abilities in language classrooms. Also, future studies employing qualitative or mixed methods can be conducted with sample groups from different educational levels to provide an in‐depth examination of the advantages and disadvantages of online and face‐to‐face problem based learning. Lay Description: What is already known about this topic: Although the positive effect of problem based learning on critical thinking was proven in other disciplines, especially in medical education, it is a relatively new concept for EFL context.Problem based learning can enhance learning outcomes.Problem based learning is effective to promote critical thinking skills and dispositions.Online problem based learning has important potential to enhance learning outcomes as well as critical thinking.The capacity of online problem based learning to enhance learning outcomes in EFL classroom as well as critical thinking is still worth exploring, especially in higher education. What this paper adds: Problem based learning, either online or face‐to‐face, significantly enhanced EFL learners' reading comprehension abilities and attitudes towards English as well as their critical thinking skills and dispositions.Online problem based learning is more effective to enhance reading comprehension abilities and attitudes than face‐to‐face problem based learning.Online and face‐to‐face problem based learning are equally effective in promoting critical thinking skills and dispositions in EFL classroom. Implications for practice and/or policy: As online problem based learning is a promising alternative to face‐to‐face problem based learning, universities, educators, administrators, and researchers can organize their problem based learning activities online to promote learning outcomes and cognitive abilities in language classrooms.Online problem based learning activities can be conducted online because online environments are also beneficial to overcome the problems of traditional classrooms.